2021
DOI: 10.1111/agec.12633
|View full text |Cite
|
Sign up to set email alerts
|

Crop prices, farm incomes, and food security during the COVID‐19 pandemic in India: Phone‐based producer survey evidence from Haryana State

Abstract: In March 2020, India declared a nationwide lockdown in response to the COVID‐19 pandemic. Such restrictions on mobility interrupted the normal functioning of agricultural value chains. For a sample of 1767 tomato and wheat producers in the state of Haryana, we study to what extent the lockdown limited access to inputs, labor, machinery, and markets to produce, harvest, and sell their crops. We quantify crop income reductions during the first months of the lockdown and analyze to what extent these are associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 47 publications
0
40
0
1
Order By: Relevance
“…Similarly, Imai, Kaicker, and Gaiha [ 9 ] found that rice, onion, potato, and tomato prices in three states of India (Maharashtra, Jharkhand, and Meghalaya) increased during the lockdown period. On the contrary, Ceballos, Kannan, Kramer [ 14 ] noted the price of tomatoes decreased significantly after the lockdown policy in Haryana. Prices of fruits and vegetables were also falling during the lockdown period compared to the pre-lockdown period in various states of India (Jharkhand, Assam, Andra Pradesh, Karnataka, Jammu, and Kashmir, [ 15 , 16 ]).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Similarly, Imai, Kaicker, and Gaiha [ 9 ] found that rice, onion, potato, and tomato prices in three states of India (Maharashtra, Jharkhand, and Meghalaya) increased during the lockdown period. On the contrary, Ceballos, Kannan, Kramer [ 14 ] noted the price of tomatoes decreased significantly after the lockdown policy in Haryana. Prices of fruits and vegetables were also falling during the lockdown period compared to the pre-lockdown period in various states of India (Jharkhand, Assam, Andra Pradesh, Karnataka, Jammu, and Kashmir, [ 15 , 16 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Prices of fruits and vegetables were also falling during the lockdown period compared to the pre-lockdown period in various states of India (Jharkhand, Assam, Andra Pradesh, Karnataka, Jammu, and Kashmir, [ 15 , 16 ]). In the case of wheat producer price in Haryana, the effects of COVID-19 was negligible [ 14 ]. In response to the resurgence of COVID-19, no significant changes in the wholesale prices of storable staple foods (rice and wheat flour) [ 17 ] were found in China.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations